Hukum dan Kekuasaan dalam Perspektif Islam dan Hukum Positif - Arif Wijaya (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2009)
The article discusses political authority, especially in enacting laws and regulations, from the perspective of Islam and Indonesian positive law. There are two reasons for human to making law. The first is to establish order in the society. The second is to keep up with dynamics and social changes. On the other hand, Islam has legal stipulations which determine rights and duties of every Muslim. However, such regulations will not be effective without power to implement them. Thus, the interaction between religion and state is inevitable. The separation between the two as it happens in the West is not the issue. State matters in principle is also Islamic matters because the goal is a perfect implementation of divine law on earth, be it the law concerning worldly affairs or here after.